Health care economics - Feldstein, Paul J. (New York : Delmar Publishers Inc., 1999)
Delivering the most detailed and exhaustive content available, market-leading HEALTH CARE ECONOMICS, 5th Edition demonstrates how basic economic concepts, principles, and theories can be used to think about and illustrate various health care issues. This introductory economics text is geared toward graduate students who will be medical and health services managers, administrators, or executives. The seventh edition of HEALTH CARE ECONOMICS includes recent data on the medical sector, updated figures and tables, the latest information on legislative changes affecting this industry, and new literature and research. It also provides an insightful historical perspective within which these changes are occurring.
An introduction to the economics of medical care -- The production of health : the impact of medical services on health -- An overview of the medical care sector -- Measuring changes in the price of medical care -- The demand for medical care -- The demand for health insurance -- The supply of medical care : an overview -- The market for health insurance: its performance and structure -- Market competition in medical care -- The physician services market -- The market for hospital services -- Health manpower shortages and surpluses : definitions, measurement, and policies -- The market for physician manpower -- The market for medical education : equity and efficiency -- The market for registered nurses -- The role of government in health and medical care -- The legislative marketplace -- National health insurance : an approach to the redistribution of medical care -- The market for long-term care services -- Concluding comments on the economics of medical care -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: MEDICAL ECONOMICS --